Performance Evaluation of Runoff River Type Hydropower Plants Operating in Nepal: A Case Study of Nepal Electricity Authority - Joshi, Sandeep; Shrestha, Rajendra (Journal of the Institute of Engineering, 2014)
Every power plant undergoes repair and maintenance which reduces the performance of the power plants as their condition undergoes periodic deterioration. To rectify the situation of aging and deterioration, timely evaluation of existing power plants is a must. Such that the evaluation will enable the decision maker to make decision regarding the present operation and maintenance practice: the need for modification of the practice or need to undergo rehabilitation in order to operate existing plants in a more efficient and effective way. Performance evaluation of a hydropower plant is performed .on the basis of various performance indicators. DOI: http://dx.doi.org/10.3126/jie.v10i1.10886 Journal of the Institute of Engineering, Vol. 10, No. 1, 2014 pp. 104–120